Temporary Access to Documents Containing Medical Secrecy (Criminal Procedural Aspect) - S. Y. Ablamskyi; V. V. Romaniuk (Law and Safety, 2020)
The relevance of the issue under research is due to the fact that the investigation of certain types of crimes is not possible without studying documents that contain information that may constitute medical secrecy. That is why, the procedure for temporary access to documents containing information that may constitute medical secrecy should be provided at the legislative level in order to ensure their protection.